Tradescantia crassula (Commelinaceae) naturalised outside the Americas: first records of the species in Taiwan - Su, Mong-Huai; Hassemer, Gustavo (Iheringia, Série Botânica., 2019)
We present here the first records of Tradescantia crassula Link & Otto outside the Americas, due to the discovery of populations of the species in Taiwan, on Formosa Island. The species is native to northeastern Argentina, southern Brazil, Paraguay and Uruguay, and is naturalised in Arkansas state, southeastern USA. It is not known how the species was introduced to Taiwan. We also provide an identification key to the four species of Tradescantia that occur in Taiwan.